Chrząszcze (Coleoptera) występujące w próchnie brzóz (Betula spp.) na terenie Kampinoskiego Parku Narodowego - Sawoniewicz, Michał (Leśne Prace Badawcze, 2013)
The composition and structure of beetle clusters living in rotting birch wood in Kampinos National Park was investigated. Photoeclectors were used to remove beetles from collected wood samples. Ten different research plots, each corresponding to a different forest type, were sampled every month over a 1-year period. A collection of 3256 beetles from 37 families comprising 206 species was amassed during the study. The collected beetles were divided into trophic families, species rareness, and constancy and site fidelity classes. At the more fertile sites, species only able to live on highly-decayed wood were collected (F3), also species facultatively able to live on either dying trees or decaying wood (F1), species that do not live on decayed wood (F0) and other rare species. Trophic group of carnivores (Z) provided most species on more fertile sites. At coniferous forest sites, as well as mixed deciduous forest sites, most individuals collected belonged to mycophagous and myxomycophagous trophic groups. At the other sites, the largest group of collected individuals was zoophagous. The number of rare species was positively related to site fertility. The average number of species increased in accordance with increasing site fertility, however this trend was only statistically significant when applied to moist coniferous forest (Bw) and moist mixed broadleaved forest (LMw) sites. The study revealed differences in the composition and structure of beetle clusters from different forest types. These differences were probably not directly related to site type, but more likely to the form of nature conservation imposed on a particular area and the potential number of decayed deciduous tree trunks. Two different clusters of saproxylic Coleoptera related to birch rot were distinguished: the first includes strictly protected deciduous forest types, the second contains the remaining forest types.